Metaphor Used in Elemental: Forces of Nature Movie - Insyira Nur Maeza; Agus Darma Yoga Pratama; I Wayan Ana (Universitas Sebelas Maret, 2025)
Metaphor is a beautiful way to communicate through understanding hidden meanings in language. The objectives of this research are to analyze what types the metaphor are employed in the Elemental: Forces of Nature movie and reveal the reasons behind its uses by the writer based on general cultural experiences, thoughts, and perspective. The research methodology employed in this research is descriptive qualitative. In analizing the data, the researcher uses the theory that is proposed by Lakoff (2003) about conceptual metaphor theory to identify the types of metaphor and analyzed the physical and cultural experience to conduct the reasons arise from the data. Those types of metaphor are structural metaphor where one concept is another concept, orientational metaphor where its deals with a spatial orientation that derived from our physical or cultural experiences, and ontological metaphor where it considers an abstract thing, such as event or idea as a concrete entity. The findings of this study reveal the presence of 5 phrases structural metaphor, 18 phrases of orientational metaphor, and 19 phrases ontological metaphor within the movie. From those results, the researcher concludes that there are three types of metaphor which is ontological metaphor the most frequently type that is used.